Exploring Relationship Between Brand Equity and Customer Loyalty On Mobile Telecommunications Product - Darmansyah, Muthya Rahmi (Journal of Management and Business Innovations, 2024)
Increased customer loyalty indicates to enhancement of brand equity for products and services. Customers are the benchmark of a company's success. This study aims to elaborate the brand equity dimensions on customer loyalty in the scope of the mobile telecommunications operator market whose products are cellular cards in Medan City. Purposive sampling technique was used in sampling with a total of 300 people. Data analysis processed using SPSS 24. The results of the study showed that brand equity dimensions have a significant effect on customer loyalty. This study are expected to provide additional insight for telecommunications companies in creating customer loyalty. In addition, this provides a basis for business actors to develop their strategies in planning and implementing actions in achieving company goals. Methods for this research is quantitative study. Further researchers can develop this research with qualitative methods so that it can provide more valuable knowledge and different perspectives in building customer loyalty.Keywords: Brand Association, Brand Awareness, Brand Equity, Customer Loyalty, and Perceived Quality